Bridging Motor and Cognitive Control: It's About Time!. Issue 1 (January 2020) - Ritz, Harrison; Frömer, Romy; Shenhav, Amitai
Abstract : Is how we control our thoughts similar to how we control our movements? Egger et al. show that the neural dynamics underlying the control of internal states exhibit similar algorithmic properties as those that control movements. This experiment reveals a promising connection between how we control our brain and our body.